TA‘ADDUD AL-JUMU‘AH PADA MASYARAKAT MLAJAH MENURUT MADHHAB SYAFI‘IYAH - Imamul Arifin (Institut Teknologi Sepuluh Nopember, 2017)
The jumu'ah prayer is the two raka'at performed at the time of the Zuhur prayer every Friday. Every Moslem is not considered to be denied the obligation of performing his jumu'ah prayers by performing the Zuhur praying if there are no things that allow him to leave the jumu'ah prayers. Along with the development of the era, the mosques were very developed even we can find easily in various regions. However, it turns out that not all mosques can be said that the mosque is eligible to serve as a place of jumuah prayer. One of them in Mlajah-Bangkalan area, there are some people who consider the amount of pilgrims jumuah must be in accordance with acceptable criteria. Seeing this phenomenon, at least the term baldah must be fully discussed thoroughly to facilitate in reviewing this problem